Mechanistic Study of Diaryl Ether Bond Cleavage during Palladium‐Catalyzed Lignin Hydrogenolysis. Issue 17 (20th April 2020) - Li, Yanding; Karlen, Steven D.; Demir, Benginur; Kim, Hoon; Luterbacher, Jeremy; Dumesic, James A.; Stahl, Shannon S.; Ralph, John
Abstract: Hydrogenolysis has emerged as one of the most effective means of converting polymeric lignin into monoaromatic fragments of value. Reported yields may be higher than for other methods and can exceed the theoretical yields estimated from measures of the content of lignin's most readily cleaved alkyl‐aryl ether bonds in β‐ether units. The high yields suggest that other units in lignin are being cleaved. Diaryl ether units are important units in lignin, and their cleavage has been examined previously using simple model compounds, such as diphenyl ether. Herein, the hydrogenolysis of model compounds that closely resemble the native lignin 4‐O‐5 diaryl ether units was analyzed. The results provided unexpected insights into the reactivity and partial cleavage of these compounds. The models and lignin polymer produced not only monomers, but also unusual 1, 3, 5‐ meta ‐substituted aromatics that appear to be diagnostic for the presence and the cleavage of the 4‐O‐5 diaryl ether unit in lignin. Abstract : The road less traveled : Palladium‐catalyzed hydrogenolysis of 4‐O‐5 diaryl ether lignin model compounds gives unexpected rearrangement monomer products. A mechanistic study indicates the cleavage of the diaryl ether bonds in lignin does not undergo a conventional solvolysis pathway but a Pd‐coordinated pathway. The bond cleavage is affected by the presence of phenolic groups in the lignin.